COMPARISON OF THE DISCRIMINATIVE PERFORMANCE OF FRAX AND GARVAN MODELS FOR ASSESSING FRACTURE RISK IN POSTMENOPAUSAL WOMEN WITH TYPE 2 DIABETES MELLITUS (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the prevalence of osteoporotic fractures and to compare the discriminative performance of the FRAX and GARVAN models in assessing fracture risk among postmenopausal women with type 2 diabetes mellitus in Vietnam.Methods: A descriptive cross-sectional study was conducted in 94 postmenopausal women with type 2 diabetes mellitus who attended the Departments of Endocrinology, Musculoskeletal, and Orthopedic Trauma at Nguyen Tri Phuong Hospital between August 2025 and January 2026.Results: The median age of the study population was 71 [68-75]. The prevalence of current osteoporotic fractures was 22.3%. Osteoporosis was identified in 89.1% of participants, with 53.2% at the lumbar spine and 63.8% at the femoral neck. The area under the receiver operating characteristic curve (AUC) of the GARVAN model was higher than that of the FRAX model for both 10-year major osteoporotic fracture risk (0.789 vs. 0.742) and 10-year hip fracture risk (0.759 vs. 0.713); however, these differences were not statistically significant (DeLong test, p > 0.05).Conclusions: Postmenopausal women with type 2 diabetes mellitus exhibited a relatively high prevalence of osteoporotic fractures. Both the FRAX and GARVAN models demonstrated comparable discriminative performance and were able to identify individuals with current fractures in this study population.
Keywords: Osteoporotic fracture, type 2 diabetes mellitus, postmenopausal women, FRAX, GARVAN.